2009
DOI: 10.1007/s00500-009-0466-5
|View full text |Cite
|
Sign up to set email alerts
|

Flank wear detection of cutting tool inserts in turning operation: application of nonlinear time series analysis

Abstract: It has been established that turning process on a lathe exhibits low dimensional chaos. This study reports the results of nonlinear time series analysis applied to sensor signals captured real time. The purpose of this chaos analysis is to differentiate three levels of flank wears on cutting tool inserts-fresh, partially worn and fully wornutilizing the single value index extracted from the reconstructed chaotic attractor; the correlation dimension. The analysis reveals distinguishable dynamics of cutting char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Finally we consider the t4.8k data set from the Chameleon data sets 3 . Chameleon is a hierarchical clustering algorithm developped by Karypis et al [70].…”
Section: Clustering Chameleon Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally we consider the t4.8k data set from the Chameleon data sets 3 . Chameleon is a hierarchical clustering algorithm developped by Karypis et al [70].…”
Section: Clustering Chameleon Data Setsmentioning
confidence: 99%
“…[2]. These environments cause component health state to change and the process behavior to evolve, as has been widely reported in the cases of tool wear [3,4] and pipe clogging or leaking [5,6]. Even though aging acts on the process components, "normal" conditions may be maintained regardless of some evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Teti et al [17] also described various vibration sensing techniques [18,19] to monitor flank wear in their full comprehensive survey conducted on machine monitoring techniques. Rajesh and Narayanan Namboothiri [20] conducted nonlinear time series analysis by examining the vibration signals which are occurred all through the cutting process. Ding and He [21] also researched on tool condition monitoring information attained from cutting tool vibration signals, Acoustic Emission signals, servo motor current signals, spindle and microscopy technique, based on which they developed a model among tool wear states and reliability.…”
Section: Vibration Signaturementioning
confidence: 99%
“…Their experiments on cutting forces demonstrated that the predicted results closely matched the measured data. Rajesh and Narayanan [13] monitored vibration signals produced during the cutting process and conducted nonlinear time series analysis. Their study revealed that both phase space reconstruction and correlation dimension calculations of the vibration signals increased with tool wear.…”
Section: Introductionmentioning
confidence: 99%